Cover Feature: Efficient Visible‐Light‐Driven Hydrogen Generation on g‐C3N4 Coupled with Iron Phosphide (ChemPhotoChem 7/2019). Issue 7 (27th June 2019) - Sun, Zhichao; Fujitsuka, Mamoru; Shi, Chuan; Zhu, Mingshan; Wang, Anjie; Majima, Tetsuro
Abstract : The Cover Feature illustrates the low‐cost Fe2 P as a cocatalyst hybridized with g‐C3 N4 for photocatalytic H2 generation under visible‐light exposure. The enhanced photocatalytic H2 generation performance was attributed to the effective interfacial charge transfer between Fe2 P and g‐C3 N4 . The study demonstrates significant potential for the application of noble‐metal‐free Fe2 P. More information can be found in the Article by Z. Sun et al. onpage 540 in Issue 7, 2019 (DOI:10.1002/cptc.201800260 ).